Impact of stator slot geometry on the windage loss in a high‐speed linear switched reluctance motor - Arjun Seshadri; Natesan C. Lenin; Sanjeevikumar Padmanaban; Baseem Khan (IET Electric Power Applications, 2022)
Abstract A linear switched reluctance motor (LSRM) is designed for electric propulsion application in a Magnetically Levitated (Maglev) train with the base speed of 7.6 m/s and operating at a maximum of 27.8 m/s. In such high‐speed LSRMs, windage loss is one of the key issues of concern. Usually, windage loss accounts for approximately 0.5% below the base speed, 20% above the base speed, and 45% at higher speeds of the total loss of the LSRM. One of the many parameters affecting this windage loss is the stator slot profile. This research work studies about different stator slot structures, thereby aiming to reduce the windage loss through computational fluid dynamics analysis. Furthermore, experimental testing of the LSRM is also done to verify the simulation results.